1974
DOI: 10.1111/j.1600-0560.1974.tb00201.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Triiodothyronine in Healing of Deep Dermal Burns and Marginal Scars of Skin grafts. A Histologic Study

Abstract: The effect of Triiodothyronine (T3) was evaluated in the healing of deep dermal burns and marginal scars of skin grafts in a group of 20 male Sprague‐Dawley rats versus a control series. Histologic examination revealed obvious differences, characterized by better organization of collagen bundles, fewer retraction spaces and smoother scars in the T3 treated group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Recent findings have shown that hypothyroidism in mice retards wound healing relative to euthyroidism (Safer et al, 2004;Safer et al, 2005). In contrast, prior reports examining the effects of THs on wound healing have been contradictory, even when THs were administered similarly (Lennox and Johnston, 1973;Zamick and Mehregan, 1973;Mehregan and Zamick, 1974;Erdogan et al, 1999). Ambiguities have also resulted from studies on keratin expression.…”
Section: Function Of Ths In Development and Homeostasismentioning
confidence: 74%
“…Recent findings have shown that hypothyroidism in mice retards wound healing relative to euthyroidism (Safer et al, 2004;Safer et al, 2005). In contrast, prior reports examining the effects of THs on wound healing have been contradictory, even when THs were administered similarly (Lennox and Johnston, 1973;Zamick and Mehregan, 1973;Mehregan and Zamick, 1974;Erdogan et al, 1999). Ambiguities have also resulted from studies on keratin expression.…”
Section: Function Of Ths In Development and Homeostasismentioning
confidence: 74%
“…T 3 is one of the most potent stimulators of growth, metabolic rate with a potential role for wound healing and also enhances recovery from stress 3 . It was also shown to heal deep dermal burns by improving the organization of collagen bundles and smoothen the scars 11 . The normal serum level of T 3 is approximately 1.5-3.1 nmol/L 5 .…”
Section: Introductionmentioning
confidence: 99%
“…An increase in thyroid hormone delivered in drinking water improved the quality of wound healing in euthyroid rats leaving less scar tissue [14,15]. Several reports recommend thyroid therapy for hypothyroid patients undergoing radiation-induced neck fistulae [16-18].…”
mentioning
confidence: 99%